2022
DOI: 10.31234/osf.io/axq49
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Finding pattern in the noise: Persistent implicit statistical knowledge impacts the processing of unpredictable stimuli

Abstract: Previous research recognized that humans could extract statistical regularities of the environment to automatically predict upcoming events. However, it has remained unexplored how the brain encodes the distribution of statistical regularities if it continuously changes. To investigate this question, we devised an fMRI paradigm where participants (N = 32) completed a visual four-choice reaction time (RT) task consisting of statistical regularities. Two types of blocks involving the same perceptual elements alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The role of the cerebellum in sequence learning is highly uncertain in the literature (Baetens et al 2020;Janacsek et al 2020). While the detrimental effect of cerebellar damage on sequence learning assumes its essential role (Dirnberger et al 2013;Doyon et al 1997;Gomez-Beldarrain et al 1998;Shin and Ivry 2003), neuroimaging studies do not always support this hypothesis (Janacsek et al 2020;Kóbor et al 2022;Seidler et al 2002;van der Graaf et al 2006). However, a recent fMRI study revealed that the cerebellum is involved in the early phase of task performance and coordination since its activity diminishes as the task becomes well practiced (Hermsdorf et al 2020).…”
Section: 2' Inhibitory' and 'Facilitatory' Rtms Protocolsmentioning
confidence: 99%
“…The role of the cerebellum in sequence learning is highly uncertain in the literature (Baetens et al 2020;Janacsek et al 2020). While the detrimental effect of cerebellar damage on sequence learning assumes its essential role (Dirnberger et al 2013;Doyon et al 1997;Gomez-Beldarrain et al 1998;Shin and Ivry 2003), neuroimaging studies do not always support this hypothesis (Janacsek et al 2020;Kóbor et al 2022;Seidler et al 2002;van der Graaf et al 2006). However, a recent fMRI study revealed that the cerebellum is involved in the early phase of task performance and coordination since its activity diminishes as the task becomes well practiced (Hermsdorf et al 2020).…”
Section: 2' Inhibitory' and 'Facilitatory' Rtms Protocolsmentioning
confidence: 99%
“…The task has been employed to study a wide array of questions, ranging from the developmental trajectory of implicit and explicit learning (Nemeth, Janacsek, & Fiser, 2013a) to the effect of instruction on automatization and rewiring (Szegedi-Hallgató et al, 2017). It has been used with EEG (Horváth et al, 2021;Kóbor et al, 2019Kóbor et al, , 2021Takács et al, 2021), non-invasive brain stimulation (Ambrus et al, 2020;Janacsek et al, 2015;Zavecz, Horváth, et al, 2020a), and both structural (Bennett et al, 2011) and functional MRI (Kóbor et al, 2022). It has also been employed to gain insight into both atypical neurocognitive development (Csábi et al, 2016;Nemeth, Janacsek, Balogh, et al, 2010a;Simor et al, 2017;Takács et al, 2018;Tóth-Fáber, Tárnok, Janacsek, et al, 2021a;Tóth-Fáber, Tárnok, Takács, et al, 2021b) and neurological or psychiatric disorders (Janacsek et al, 2018;Nemeth, Janacsek, Király, et al, 2013b;Unoka et al, 2017).…”
Section: Introductionmentioning
confidence: 99%